2013
DOI: 10.1002/brb3.154
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of subcortical gray‐matter vascularization using 7 Tesla time‐of‐flight angiography

Abstract: Background The integrity of subcortical brain nuclei is associated with maintenance of regular cognitive performance levels and has been shown to be particularly affected by aging-related vascular pathology. This study aims to demonstrate applicability of high field strength magnetic resonance angiography at 7 Tesla (7T) for assessment of interindividual variation in subcortical vascularization. Methods Two healthy female subjects without known history of cerebrovascular disease or malformation, aged 43 and 86… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Although the vesselness filter for the 3D rendering loses small details, an improved segmentation algorithm could enable vessel morphology to advance our understanding of the neurovascular structure–function relationship . Motion‐prone cohorts could be studied in vivo to visualize previously not detectable changes in vascularization of, for example, the striatum or hippocampus, potentially improving the knowledge about neurodegenerative diseases, stroke, and aging . Furthermore, motion‐corrected TOF angiography could improve functional MR angiography , which detects changes of the arterial microvasculature due to stimuli at high spatial resolutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the vesselness filter for the 3D rendering loses small details, an improved segmentation algorithm could enable vessel morphology to advance our understanding of the neurovascular structure–function relationship . Motion‐prone cohorts could be studied in vivo to visualize previously not detectable changes in vascularization of, for example, the striatum or hippocampus, potentially improving the knowledge about neurodegenerative diseases, stroke, and aging . Furthermore, motion‐corrected TOF angiography could improve functional MR angiography , which detects changes of the arterial microvasculature due to stimuli at high spatial resolutions.…”
Section: Discussionmentioning
confidence: 99%
“…For the first time, the microvasculature supplying the deep brain structures such as lenticulostriate arteries (LSA) was visualized noninvasively, potentially enhancing the knowledge about lacunar infarcts or small vessel diseases (e.g., leukoaraiosis) . Aging decreases the vascularization of subcortical nuclei, as shown by interindividual analysis . Also, neurodegenerative diseases such as Alzheimer's disease and Parkinson's disease and multiple sclerosis are suspected to have a vascular component .…”
Section: Introductionmentioning
confidence: 99%
“…The study suggested that thickening of the wall does not necessarily lead to the luminal narrowing, what was confirmed by the Liem et al [39]. The technique has been used to evaluate the condition of small subcortical vessels, particularly vulnerable in the aging process [29].…”
Section: Discussionmentioning
confidence: 72%
“…Visualization for the small perforating vessels of the Circle of Willis, that are not fully visualized using low-field-strength MRA is improving with increasing magnetic field strength, which has been proved by several studies [23][24][25][26][27][28][29][30]. Nowinski et al [24] compared the visualization of small cerebral vessels (their length and volume) and proved that both values increased with field strength, missing 6% of the vasculature volume using 3 T MRA and only 1% using 7 T MRA.…”
Section: Discussionmentioning
confidence: 93%
“…Here, a dual‐echo technique was used visualizing the arterial side of the vasculature using TOF MRA (first echo) and imaging the venous bed by taking advantage of the BOLD‐based signal difference between venous blood and surrounding tissue (second echo). Proving the capability of UHF‐MRA to answer neuroscientific questions, TOF‐MRA at ultra‐high field strength was used to show aging‐related changes in vascularization, which were most pronounced in the thalamus and the pallidum .…”
Section: Structural Imagingmentioning
confidence: 99%